Implementation of Ethnoscience to Improve Elementary School Students' Critical Thinking Ability in Science Learning - Munira, Intan; Mulyadi, Mulyadi; Ramadhan, MFirman (JUPE : Jurnal Pendidikan Mandala, 2024)
This study discusses the importance of integrating ethnoscience into elementary school education to enhance students' understanding of local culture as well as their interest and motivation in science. The ethnoscience approach, which connects scientific knowledge with culture and local wisdom, can make learning more meaningful and relevant to students' daily lives. The research method used is empirical juridical with a descriptive qualitative approach through interviews and documentation. The results of the study show that ethnoscience-based learning can improve students' critical, creative, and systematic thinking skills, as well as foster a love for their culture and environment. The implementation of ethnoscience in the Indonesian education curriculum not only increases students' science literacy but also helps them apply scientific knowledge to solve real-life problems. Therefore, the development of ethnoscience-based learning models and methods is essential to support students' interest and academic achievement in science.